The Impact of Early Marriage on Minors and the Legal Problems That Arise (Journal of Civil Criminal Law, 2025)
Marriage involves individual rights such as opinion, privacy and non-discrimination. Early marriage is the practice of marriage involving one or both partners who are still young, where both are still under the legal age or generally recognized age of adulthood. Early marriage can be influenced by various factors, namely social, economic, cultural and educational pressures. Family involvement, cultural norms, and gender inequality can also play an important role in the decision to marry early. Early marriage of minors creates a number of legal problems, which involve violations of children's rights and also gender inequality. The age for marriage must be completely mature, which is 19 years for men and 16 years for women. If both of them are still young, or you could say like young onions, their marriage will always be filled with problems. Both of them still have the same high level of ego, are still children and still only think for a few days. In Indonesia, Law no. 1 of 1974 concerning early marriage, namely the minimum age for marriage. Law no. 16 of 2019, regulates the second amendment to Law no. 1 of 1974 confirms that the minimum age limit is 19 years for men, and 16 years for women. A woman is someone who has reproductive organs which are related to the ability to give birth to children. Meanwhile, a man is someone who has reproductive organs that play a role in reproduction itself. In Indonesia, the case of early marriage is still a very serious and vulnerable issue. As reported by the KEMENKO PMK, it was stated that there were around 1.2 million cases of early marriage in Indonesia. Where, the proportion of women aged 20-24 years who were married before the age of 18 was 11.21% of the total number of children. This means that around 1 in 9 women aged 20-24 years were married as children. Meanwhile, around 1 in 100 men aged 20-24 years were married as children. Due to the large number of cases regarding underage marriage, the government's role must be agile and fast in dealing with important cases like this. The government must play a role in preventing how to prevent cases of underage marriage from increasing every year.